2010
DOI: 10.2528/pier10080805
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Reconstruction for Sar Imaging Based on Compressed Sensing

Abstract: Abstract-Synthetic Aperture Radar (SAR) can obtain a twodimensional image of the observed scene. However, the resolution of conventional SAR imaging algorithm based on Matched Filter (MF) theory is limited by the transmitted signal bandwidth and the antenna length. Compressed sensing (CS) is a new approach of sparse signals recovered beyond the Nyquist sampling constraints. In this paper, a high resolution imaging method is presented for SAR sparse targets reconstruction based on CS theory. It shows that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 18 publications
(24 reference statements)
0
97
0
Order By: Relevance
“…. , N TC }, is arranged in descend order as, (16) where N P m [1] denotes the largest entry. The sudden change between N P m [k] and N P m [k + 1] is caused by the large difference between the number of points in the true track and the false track.…”
Section: The Proposed Cs-tbd Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…. , N TC }, is arranged in descend order as, (16) where N P m [1] denotes the largest entry. The sudden change between N P m [k] and N P m [k + 1] is caused by the large difference between the number of points in the true track and the false track.…”
Section: The Proposed Cs-tbd Algorithmmentioning
confidence: 99%
“…A great deal of compressed sensing based methods have been applied to radar systems [8][9][10][11][12][13][14][15][16][17][18], which recover the target scene from fewer measurements than traditional methods. In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the theory of compressed sensing (CS) has attracted increased research interests to deal with the imaging problem when the data set is obtained not following Nyquist theory [12,13]. However, CS-based reconstruction still belongs to the scope of discrete parameter estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], Baraniuk and Steeghs suggest to apply CS to radar imaging. After that, the CS based SAR imaging [6,7], ISAR imaging [8,9] and other applications of microwave imaging [10][11][12] are extensively discussed. A more detailed and comprehensive account can be found in [4,13,14].…”
Section: Introductionmentioning
confidence: 99%